2021
DOI: 10.1061/(asce)mt.1943-5533.0003874
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Roll-Threading Superelastic Cu-Al-Mn SMA Rods

Abstract: This paper examines the feasibility of roll-threading superelastic Cu-Al-Mn shape memory allow (SMA) rods. The key idea behind this study was to perform roll-threading between quenching and aging, where cold workability of the material is relatively high. To obtain excellent superelasticity, single-crystal superelastic Cu-Al-Mn SMA rods were prepared with 16-mm diameter and 300-mm length. Threadability was studied by dimensional inspection and surface observations. Mechanical properties of the threaded rods we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Omori et al [54], showed that by using proper cyclic heat treatment, i.e. abnormal grain growth, it is feasible to produce CAM SEAs with a single grain size over 700 mm [55,56]. Compared to single crystal CAM SEAs, polycrystal ones are more cost efficient because an intensive heat treatment is not required.…”
Section: Methodsmentioning
confidence: 99%
“…Omori et al [54], showed that by using proper cyclic heat treatment, i.e. abnormal grain growth, it is feasible to produce CAM SEAs with a single grain size over 700 mm [55,56]. Compared to single crystal CAM SEAs, polycrystal ones are more cost efficient because an intensive heat treatment is not required.…”
Section: Methodsmentioning
confidence: 99%